The study of living control systems : a guide to doing research on purpose - Marken, Richard S., 1946- (Cambridge : Cambridge University Press, 2021)
This book is a guide to doing a new kind of psychological research that focuses on the purposes rather than the causes of behavior. The research methods described here are based on a theory of behaviour called Perceptual Control Theory (PCT) that views organisms as purposeful rather than mechanical systems. According to PCT, purposeful behaviour involves acting to control perceptual input variables. Thus, understanding the purposeful behaviour of living organisms is a matter of determining the perceptual variables they are controlling when they are carrying out various behaviors. This book outlines research methods that determine what perceptual variables an organism is controlling, how it controls those variables, and why. It also describes methods for studying how an organism develops the ability to control different perceptions and how consciousness might be involved in this process.
Title from publisher's bibliographic system (viewed on 08 Feb 2021).
Keywords: Psychology -- Research; Human behavior; Perceptual control theory